Al-Imam Al-Nawawi's preference in his Rawdah al-Talibin : a reference to chapter of Islamic transaction / Ghotbaddin Zahedian - Zahedian, Ghotbaddin (2015)
This study sought to investigate the preferences of Imām Al-Nawawī in the field of transactions based on the book Rawdah al-Tālibīn, starting from the chapter of sales until the section on alms. The importance of this topic is based on the status of Imām Al-Nawawī’s preferences among the scholars of Islamic jurisprudence in general and particularly among the Shāfi`ī scholars. He is credited with reviewing the Shāfi`ī school of jurisprudence, editing it, adjusting it, and refining it, in addition to the status of the book Rawdah al-Tālibīn in the Shāfi`ī school of jurisprudence. Despite the status of Imām Al-Nawawī’s preferences, there is a problem that calls for studying these preferences, namely the variances in preferences and a djustments throughout the books of Imām Al-Nawawī. For instance, in some of his books he makes preferences that are in contrast with those which he made in other books, which created a dispute among the scholars of Islamic jurisprudence in determining the final preferences of Imām Al-Nawawī. This study aims to reveal the reasons why the scholars of the Shāfi`ī school of jurisprudence rely upon the works of Imām Al-Nawawī over those of other scholars of the school, while clarifying the criteria of preference followed by Imām Al-Nawawī, deriving his preferences in the field of transactions from the book Rawdah al-Tālibīn, clarifying the reasons of variance between his preferences throughout his most prominent books of Islamic jurisprudence, and deriving the stance of the Shāfi`ī school of jurisprudence through these preferences. This was achieved by studying these preferences in a comparative, critical manner, by comparing between his preferences in the field of transactions from the book Rawdah al-Tālibīn with those in his most prominent books of Islamic jurisprudence and the preferences of Imām Al-Rāfi`ī and those of other scholars of the Shāfi`ī school of jurisprudence. Then the preferences were analysed by perusing the book Rawdah al-Tālibīn and the most prominent books of Imām Al-Shāfi`ī in various fields of Islamic jurisprudence, by clarifying the points of conformity and difference between these preferences among his various books, concluding with the final stance of Imām Al-Nawawī. This is followed by mentioning the most prominent stances of the Shāfi`ī school of jurisprudence.among the findings are Imām Al-Nawawī set criteria for comparing between difference stances in the Shāfi`ī school of jurisprudence. Through these criteria he edited and corrected the Shāfi`ī school of jurisprudence. Among the reasons that led to the variances in Imām Al-Nawawī’s preferences: writing different books in various periods of time, and that many of his volumes were written while he was still seeking knowledge. The majority of Imām Al-Nawawī’s preferences fall into the scope of the Shāfi`ī school of jurisprudence. His preferences in his book Rawdah al-Tālibīn either contrast with those mentioned in his other books, or contrast with the preferences of Imām Al-Rāfi`ī, or fall totally outside the scope of the Shāfi`ī school of jurisprudence, yet the latter are very few.